NCAA Division I Athlete STEM Graduates - Eddie Comeaux; Whitney Griffin; Patina Bachman; Jeff Porter (University of Kansas Libraries, 2017)
The purpose of this study was to explore how NCAA Division I athlete STEM graduates viewed their undergraduate experiences with members of the campus community such as academic advisors, other athletes, faculty, nonathlete students, and coaches. Using several interpretive frameworks, this study found that stereotypical assumptions, whether positive or negative, were conditional upon the athlete's gender. Moreover, male athletes reported feeling a level of acceptance from campus members, although this same experience was eventually interpreted as token or conditional acceptance, largely because they were subjected to salient athlete microaggressions and considered exceptional but not entirely accepted by the academic community. The study also discovered that athletes who pursued degrees in STEM fields engaged in in-group stereotyping of other athletes, and some were aware of the social significance of race and intersectional identities in shaping the quality of their college experiences. These findings have implications for faculty, student affairs professionals, and others who frequently interact with college athletes and are committed to creating more equitable educational environments.